Pemilihan Jajanan Anak Sekolah Dasar Mardi Lestari Kecamatan Medan Petisah Kota Medan - Neni Ekowati Januariana; Hasariaman Zebua (LPPM STIKES Siti Hajar dan Insight Power, 2022)
An adequate nutrition knowledge will instill good habits and use of food ingredients..Objectives to determine the relationship between knowledge with attitudes of primary school students in the selection of snacks at the Mardi Lestari Foundation in Medan Petisah sub-district, Medan. Method; The design of this study is analytical survey research method with cross sectional design. The population of this study were 72 students, and all of them were made as research samples which constituted the total population..Result frequency distribution of 72 students with less knowledge was 57 students (79.2%), and good knowledge was 15 students (20.8%). Frequency distribution of 72 students based on negative attitudes as many as 55 students (76.4%), and positive attitudes as many as 17 students (23.6%). Chi square test results obtained the value of ρ value 0 .016 <0.005). Conclusion there is a relationship between the knowledge of the attitudes of primary school students in selecting of snacks in the Mardi Lestari Foundation, Medan Petisah Sub-District..Keywords: Knowledge, Attitude of Snack Food Selection